NEEDS ANALYSIS OF ENGLISH LEARNING FOR STUDENTS OF ECONOMIC DAN BUSINESS UDAYANA UNIVERSITY - Saientisna, Made Detriasmita (Lingual Journal of Language and Culture; Vol 7 No 1 (2019): Lingual: Journal of Language and CultureDO - 10.24843/LJLC.2019.v07.i01.p04, 2019)
To face the Asian Economic Community, active mastery of English is very important so that people can compete with good workers from their own area or workers from other Asian countries. This study aims to find out (1) whether the problems faced by the students of the Faculty of Economics, Udayana University in learning English and (2) whether the English language needs needed by economic students at the Faculty of Economics and Business, Udayana University to design the correct syllabus and effective in teaching English. Analysis of English language needs is done by giving questionnaires to students for their answers, those questions concerning the field of English what they are very proficient (speaking, listening, reading and writing) and which areas of English they find difficult to learn, and choose what lessons they think are necessary that have not been provided in the current syllabus. The answers from these students will be analyzed according to the need analysis by Hutchinson and Waters (1994) and Dudley-Evans and St. John (1998). From this research, it is expected that students can improve their English language skills in economics majors and also can design a new syllabus that is more effective in accordance with the needs of students at the Faculty of Economics, Udayana University.   Key words: Needs analysis, english language, english for economic, ESP.